PELAKSANAAN TUGAS PEGAWAI BADAN PENGAWAS PEMILIHAN UMUM (BAWASLU) PROVINSI RIAU PADA PEMILIHAN GUBERNUR TAHUN 2018 - Mollyta Anastasya; Harapan Tua RFS (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The Election Supervisory Agency (BAWASLU) of Riau Province is an institution that oversees the holding of the General Elections in the area of Riau Province. In the Election of the Governor of Riau Province in 2018, supervision conducted by the Riau Province Election Supervisory Body was still not optimal. Can be seen from the findings of cases of violations such as campaigns outside the schedule, installing APKs not in accordance with the Law, Black Campaigns and Money Politics. The purpose of this study was to see how the implementation of the Riau Province Bawaslu's duties in the Election of the Governor of Riau Province in 2018 as well as what factors hindered the implementation of the Riau Province Bawaslu's duties in the Election. This research is a descriptive study using qualitative methods. The selection of informants in this study uses incidental sampling techniques. Data collection is done through interviews, observations (direct observation) and documentation. The theoretical concept used in this study is the theory of task implementation by Suprihanto (1988: 102), with indicators of task mastery, ability to cooperate, finish work on time, and provide timely report results. Based on the results of the study it can be concluded that the implementation of the tasks of the Riau Election Supervisory Agency is still not effective. This is because some staff still find it difficult to understand their duties. In addition there is an unfavorable relationship with other parties involved in the election. And also the lack of transportation facilities in Bawaslu, Riau Province. *Keywords: Task Implementation, Cooperation